Primary Immunodeficiency with Severe Multi-Organ Immune Dysregulation. (28th December 2019) - Gavrilova, Tatyana
Abstract : Polyglandular autoimmune syndrome type 1, also known as autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), is a rare primary immunodeficiency disorder with multi-organ involvement. Besides for being predisposed to severe life-threatening infections, patients with APECED are also prone to organ impairment secondary to severe autoimmunity. As this is an autosomal recessive disorder, a biallelic mutation in the AIRE gene is responsible for APECED. The author presents a case of APECED with a single AIRE mutation. Whole exome sequencing identified a mutation in the BTNL2 gene that the author suggests may have contributed to the patient's presentation.